Governance with and of AI: The role of ethics, equity, and trustworthiness - REMOLINA LEON, Nydia (Institutional Knowledge at Singapore Management University, 2023)
This blog from the Area 4 Committee (Focus on Ethics, Equity & Trustworthiness) working across the Data for Policy Conference and Data & Policy journal discusses the lines of inquiry related to the question of how AI and data systems can improve governance and invites contributions by the 27th November deadline of the 2024 Conference.